PENGARUH HARGA, KUALITAS PRODUK, DAN SISTEM PEMBAYARAN COD (CASH ON DELIVERY) TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE DI KECAMATAN PARE - Saputra, Fernanda Bagus; Samari, Samari; Sardanto, Rino (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this study was to determine the effect of price, quality of goods, and the COD payment system on purchasing decisions either partially or simultaneously. This study uses a quantitative approach with the regression method. The sample used in this study included 40 consumers and was analyzed using multiple linear regression with SPSS for windows version 22. The conclusions from this research are (1) price partially has no significant effect on purchasing decisions at the shopee marketplace in Pare District. Indonesia, while product quality, the COD payment system partially has a significant effect on financial performance in purchasing decisions at the shopee marketplace in Pare District. (2) product quality, and the COD payment system simultaneously and significantly influence purchasing decisions at the shopee marketplace in Pare District.